Women’s movements and the State in Portugal:: a State feminism approach - Monteiro, Rosa; Ferreira, Virgínia (Sociedade e Estado, 2016)
This paper aims to contribute towards a better understanding of the dynamics of women’s movements and their relations with institutions, political parties and the official mechanisms used to promote gender equality. It is the outcome of the first study on State feminism in Portugal. Our research was carried out using a case study which focused on the main gender equality official mechanism and its networks, which required a qualitative approach. We concluded that currently, while the Portuguese State is confronted with its persistent inability to implement gender equality policies, the present situation of Portuguese women’s movements is that of redefining and adjusting to the major challenge of reinvention and resignification within a very difficult external environment.